Electrical stimulation of the auricular branch of the vagus nerve potentiates analgesia induced by physical exercise in mice with peripheral inflammation - Dutra, Aline Raulino; Salm, Daiana Cristina; da Silva, Rafaela Hardt; Tanaka, Fernanda; Lutdke, Daniela Dero; de Oliveira, Bruna Hoffmann; Lampert, Rose; Bittencourt, Edsel B.; Bianco, Gianluca; Gadotti, Vinícius M.; Reed, William R.; Mack, Josiel Mileno; et al. (Frontiers in Integrative Neuroscience, 2023)
Objective This study evaluated the antihyperalgesic and anti-inflammatory effects of percutaneous vagus nerve electrical stimulation (pVNS) associated with physical exercise, i.e., swimming, in mice with peripheral inflammation. Methods The pain model was induced by intraplantar (i.pl.) injection of Freund’s complete adjuvant (CFA). Sixty-four male Swiss mice (35–40 g) received an i.pl. of CFA and underwent behavioral tests, i.e., mechanical hyperalgesia, edema, and paw temperature tests. Additionally, cytokine levels, specifically interleukin-6 (IL-6) and interleukin-10 (IL-10), were determined by enzyme-linked immunosorbent assay. Mice were treated with swimming exercise for 30 min alone or associated with different time protocols (10, 20, or 30 min) of stimulation in the left ear with random frequency during four consecutive days. Results pVNS for 20 min prolonged the antihyperalgesic effect for up to 2 h, 24 h after CFA injection. pVNS for 30 min prolonged the antihyperalgesic effect for up to 7 h, 96 h after CFA injection. However, it did not alter the edema or temperature at both analyzed times (24 and 96 h). Furthermore, the combination of pVNS plus swimming exercise, but not swimming exercise alone, reduced IL-6 levels in the paw and spinal cord, as well as IL-10 levels in the spinal cord. Conclusion pVNS potentiates the analgesic effect induced by swimming, which may be, at least in part, mediated by the modulation of inflammatory cytokines in the periphery (paw) and central nervous system (spinal cord). Therefore, the combination of these therapies may serve as an important adjunctive treatment for persistent inflammatory pain.